A tracer gas leak rate measurement method for circular air circuits. (March 2016) - Tiddens, Arne; Röger, Marc; Stadler, Hannes; Hoffschmidt, Bernhard
Abstract: Qualitative measurements of leaks in air flows are frequently conducted in engineering. However, an environmentally friendly leak rate measurement technique which yields quantitative results and is applicable to hot, large-scale circular air flows (≈10 kg/s; ≈ 700 °C) with high leak rates has not been presented yet. This paper describes the development, test and validation of a stationary and a dynamic, helium based tracer gas method on a lab-scale model of a solar air receiver with partial air recirculation. Helium is chosen as tracer gas since it is environmentally friendly, stable under high temperatures and is also cheap for large-scale air flows. The tracer gas is injected either continuously or intermittently into the model system, its concentration is measured using a mass spectrometer and the static or dynamic concentration response of the system is used to determine the leak rate. The stationary method needs two measurement points upstream and downstream the leak, the dynamic method only one measurement point if applied to a circular air flow system. Since the dynamic method is time dependent the transfer function of the measurement setup was determined and the dynamic measurement error was considered. An extensive uncertainty analysis is presented for both the stationary and the dynamic method. Exemplary measurements were conducted at the model system with very good results. Both dynamic and static measurements yield the same result within their confidence intervals. The leak rate of the solar receiver model with a mass flow rate of m ̇ in = ( 0.247 ± 0.008 ) / kg s was measured to be l stat = ( 36.1 ± 2.3 ) % and l dyn = ( 34.5 ± 3.6 ) % with the static and the dynamic method respectively. Abstract : Highlights: A tracer gas method is developed for hot, large, circular air flows with large leaks. Environmentally friendly and thermally stable helium is used as tracer. The developed method needs only one measurement point to determine the leak rate. Dynamic error corrections for dynamic helium concentration measurement are developed. A rigorous uncertainty analysis for both static and dynamic measurements is shown. Measurements on a lab-scale model of a solar receiver are presented.